ANALYSIS OF THE MANAGEMENT OF SCIENCE LEARNING AT SMPS TRI BHAKTI PEKANBARU - Tanjung, Azzahra Faudie (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to see how lesson planning, implementation of learning and assessment of student learning outcomes at SMPS TRI BHAKTI PEKANBANBARU. The research method used is qualitative research. This study uses data collection techniques by interview. The results of the research that were obtained were that the lesson plan was made by the teacher himself whose components were adjusted to the RI Minister of National Education Number. 41 of 2007. However, there were several components that the researcher did not encounter in the field, one of which was in the core activities the researcher found that at the third meeting using the Discovery learning method it was not in accordance with the learning steps in the lesson plans, namely no experiments and allocations time that is not in accordance with the RPP has been made.Keywords: Management, Learning, Dynamic Electricity